Bronchoscopic techniques in the management of patients with tuberculosis - Mondoni, Michele; Repossi, Alice; Carlucci, Paolo; Centanni, Stefano; Sotgiu, Giovanni (International journal of infectious diseases, 2017)
•Bronchoscopy can be crucial for pulmonary TB diagnosis.•Bronchoscopic needle aspiration techniques are safe.•Bronchoscopic therapy can be helpful in the treatment of endobronchial TB. Tuberculosis (TB) is one of the leading causes of morbidity and mortality worldwide. Early diagnosis and treatment are key to prevent Mycobacterium tuberculosis transmission. Bronchoscopy can play a primary role in pulmonary TB diagnosis, particularly for suspected patients with scarce sputum or sputum smear negativity, and with endobronchial disease. Bronchoscopic needle aspiration techniques are accurate and safe means adopted to investigate hilar and mediastinal lymph nodes in cases of suspected TB lymphadenopathy. Tracheobronchial stenosis represents the worst complication of endobronchial tuberculosis. Bronchoscopic procedures are less invasive therapeutic strategies than conventional surgery to be adopted in the management of TB-related stenosis. We conducted a non-systematic review aimed at describing the scientific literature on the role of bronchoscopic techniques in the diagnosis and therapy of patients with TB. We focused on three main areas of interventions: bronchoscopic diagnosis of smear negative/sputum scarce TB patients, endobronchial TB diagnosis and treatment and needle aspiration techniques for intrathoracic TB lymphadenopathy. We described experiences on bronchoalveolar lavage, bronchial washing, and biopsy techniques for the diagnosis of patients with tracheobronchial and pulmonary TB; furthermore, we described the role played by conventional and ultrasound-guided transbronchial needle aspiration in the diagnosis of suspected hilar and mediastinal TB adenopathy. Finally, we assessed the role of the bronchoscopic therapy in the treatment of endobronchial TB and its complications, focusing on dilation techniques (such as balloon dilation and airway stenting) and ablative procedures (both heat and cold therapies).